Assessment of hydrodynamic pressure effect on backhoe-loader movement to wade through the water obstacle - Ye. R. Magdina (Вестник СибАДИ, 2024)
Introduction. Hydrodynamic pressure plays an essential role in the operation of transport and technological machines used in flooded areas for recovery and emergency actions. The study of this influence has a great relevance due to the necessity of improving the work efficiency and safety in water environment. Hydrodynamic pressure can cause changes in machine operation and influence on its maneuverability and stability. Understanding of these processes allows to develop more effective methods to prevent the negative impact consequences of the water on the machine performances, let us evaluate the safe conditions of their use.   The aim of the study of hydrodynamic pressure effect on transport and technological machine movement to wade through the water impediment, using the example of an all-wheel drive excavator-loader with equal-sized wheels, is to determine the critical values of the water barrier parameters, which ensure effective and safe overcoming of water obstacles by this type of vehicle.   Materials and methods. Theoretical studies related to the influence of water flow on the movement of self-propelled wheeled machines were used for the analysis. Mathematical modelling of rectilinear movement of backhoe-loader through the water barrier of different depth and with different flow velocity was carried out. Transverse (frontal) hydrodynamic resistance, longitudinal (lateral) hydrodynamic pressure and standard reactions on the machine wheels were taken as the main parameters under study.   Results. Mathematical relationships were derived to determine the standard reactions on the front and rear axles of the excavator-loader under the influence of transverse hydrodynamic resistance in standing water, normal reactions on the left and right sides of the machine under the influence of longitudinal hydrodynamic pressure on the stationary and moving machine, graphical relations of normal reactions of the wheels depending on the depth of the water stream were deduced.   Discussion and conclusion. The presence of unfavorable factors of the water environment effecting the movement of transport and technological machines through the water obstacle provides the basis for the development of a methodology for determining the maximum flooding parameters at which machines can perform work safely and effectively in flooded areas. The study of the influence of hydrodynamic pressure on transport and technological machines is an important task aimed at solving this problem. The obtained results will help to develop machine building techniques and technologies for operation in conditions with increased hydrodynamic pressure, which contributes to the development of industries related to the operation of land transport and technological machines in the aquatic environment.